HYGRO-THERMO-MECHANICAL PROPERTIES OF EARTHEN MATERIALS FOR CONSTRUCTION: A LITERATURE REVIEW - Moevus, Mariette; Anger, Romain; Fontaine, Laetitia (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Although earth has been used in construction for millennia and is still one of the most widely used building materials in the world, it is dificult to ind reliable values of hygro-thermal and mechanical properties of earthen materials. Little scientiic research has been conducted on this material compared to the huge amount of literature available for cementitious materials. Considering the literature on earthen materials, a majority of studies deal with cement stabilized earth for compressed-earth blocks or rammed earth. Less has been done about natural unstabilized earth. The only existing comprehensive overview on the properties of earthen materials was authored by CRAterre-ENSAG and published 25 years ago. For the second time in its 30 years of existence, CRAterre-ENSAG has undertaken the task of re-actualizing this synthetic knowledge by writing a comprehensive review of the existing literature on the subject. In the present work, we intend to compile the most reliable experimental data on hygro-thermal and mechanical properties of natural earth. We will inventory the performances determined by several research teams for rammed earth, compressed-earth blocks, adobe, cob and mortar. We will discuss the reliability of the experimental techniques used. We will provide an overview on the state of knowledge concerning the different properties, as well as on the lacking data. Finally, this literature review will also give some orientation for further scientiic research.